2020
DOI: 10.1523/jneurosci.0801-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine Signaling and NMDAR-Mediated Synaptic Plasticity Are Regulated by System A-Type of Glutamine/D-Serine Dual Transporters

Abstract: D-serine is a physiologic coagonist of NMDA receptors (NMDARs) required for synaptic plasticity, but mechanisms that terminate D-serine signaling are unclear. In particular, the identity of unidirectional plasma membrane transporters that mediate D-serine reuptake has remained elusive. We report that D-serine and glutamine share the same neuronal transport system, consisting of the classic system A transporters Slc38a1 and Slc38a2. We show that these transporters are not saturated with glutamine in vivo and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…Together, these results highlight that genetically modified models must be studied carefully because compensatory mechanisms can mask changes in synapses by maintaining overall network activity. Nevertheless, SR-KO mice are still an excellent animal model to validate our understanding of mechanisms that are dependent on d -serine availability at the synapse, as recently shown for the role of the system A-type of glutamine transporters in terminating d -serine signaling [ 41 ] or the Asc1 subtype of neutral amino acid transporters in mediating d -serine release [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results highlight that genetically modified models must be studied carefully because compensatory mechanisms can mask changes in synapses by maintaining overall network activity. Nevertheless, SR-KO mice are still an excellent animal model to validate our understanding of mechanisms that are dependent on d -serine availability at the synapse, as recently shown for the role of the system A-type of glutamine transporters in terminating d -serine signaling [ 41 ] or the Asc1 subtype of neutral amino acid transporters in mediating d -serine release [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing synaptosomes and competitive inhibitors have identified the following d -serine transporters: the Na + -independent transporter asc-1 [ 142 , 176 , 177 , 178 ] and the Na + -dependent transporters ASCT1 [ 145 ], ASCT2 [ 178 ], and System A transporters (SAT1 and SAT2) [ 176 ]. The immunohistochemistry indicates that, within the CNS, Asc-1 is a neuronal protein concentrated in the presynaptic complexes [ 177 , 179 , 180 , 181 ]; ASCT2 is limited to neuronal dendrites and, except for retinal glia, is not found in glia [ 142 ]; ASCT1 is present on astrocytes [ 142 , 145 ]; SAT1 is expressed mainly in GABAergic neurons [ 176 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ], pyramidal neurons lack appreciable immunoreactivity [ 176 , 183 , 184 , 190 ], and SAT2 is expressed in the somatodendritic compartments of glutamatergic neurons, barely detected in interneurons, and potentially glia [ 185 , 189 , 191 , 192 , 193 , 194 , 195 ]. Although helpful in identifying transporters, synaptosomes and inhibitors, which are themselves substrates for transport, have limited use for studying d -serine regulation in vivo [ 196 ].…”
Section: Molecular Mechanisms Of Astrocyte Mediated Co-agonismmentioning
confidence: 99%
“…So far, only System A appears to accumulate intracellular d -serine in vivo. However, this relied on inhibition by the System A substrate MeAIB [ 176 ], which is also a substrate of the novel glycine transporter, SLC6A20A [ 173 ]; as such, confirmation awaits the development of a specific non-competitive inhibitor.…”
Section: Molecular Mechanisms Of Astrocyte Mediated Co-agonismmentioning
confidence: 99%
See 2 more Smart Citations